THE IMPACT OF WORKLOAD, WORK DISCIPLINE, AND JOB SATISFACTION ON NURSE TURNOVER INTENTION AT RSIA ABBY KOTA LHOKSEUMAWE - Raisya Ananta; Sullaida Sullaida; Faisal Matriadi; Khairawati Khairawati (PT. Intelek Cendikiawan Nusantara, 2025)
This study examines the effect of workload, work discipline, and job satisfaction on nurse turnover intention at RSIA Abby Kota Lhokseumawe. Turnover intention is a critical issue in healthcare organizations as it influences service quality and organizational stability. The research employed a quantitative approach using primary data collected through questionnaires distributed to all 45 nurses at RSIA Abby, selected through a saturated sampling technique. The data were analyzed using multiple linear regression with SPSS. The findings reveal that workload has a significant positive effect on turnover intention, indicating that heavier tasks and responsibilities increase nurses’ intention to leave. Conversely, work discipline and job satisfaction show significant negative effects, suggesting that higher levels of discipline and satisfaction reduce the tendency of nurses to resign. These results highlight the importance of balancing workload, fostering discipline, and enhancing satisfaction programs to mitigate turnover risks. The study concludes that effective human resource management practices are essential in reducing turnover intention and improving healthcare service quality.